Art Actuel à Liège. (Liège : la ville de Liège, 1985)
Angeli, Marc ; Bastianelli, Ariane ; Bianchini, Georges ; Bong, Rita ; Brissa, Christiane ; Collin, Jocelyne ; Couvert, Jean-Paul ; Dutrieux, Daniel ; Fauconnier, Jean-Luc ; Fourneau, Daniel ; Freson, Florence ; Haenen, Toon ; Heselmans, Suzanne ; Hoornaerts, Philippe ; Huylebroeck, Paul ; Joosen, Nic ; Klènes, Anne-Marie ; etc.
Art Actuel à Liège, Parc de la Boverie, Liège, 6 september - 6 oktober 1985
boek